Altered functional connectivity of the red nucleus and substantia nigra in migraine without aura - Xiaobin Huang (The Journal of Headache and Pain, 2019)
Abstract Background Functional connectivity (FC) has been used to investigate the pathophysiology of migraine. Accumulating evidence is pointing toward malfunctioning of brainstem structures, i.e., the red nucleus (RN) and substantia nigra (SN), as an important factor in migraine without aura (MwoA). We aimed to identify atypical FC between the RN and SN and other brain areas in patients with MwoA and to explore the association between RN and SN connectivity changes and performance on neuropsychological tests in these patients. Methods Resting-state functional magnetic resonance imaging (fMRI) data were obtained from 30 patients with MwoA and 22 age-, sex-, and years of education-matched healthy controls (HC). The FC of the brainstem structures was analyzed using a standard seed-based whole-brain correlation method. The results of the brainstem structure FC were assessed for correlations with other clinical features. Results Patients with MwoA exhibited reduced left RN-based FC with the left middle frontal gyrus, reduced right RN-based FC with the ipsilateral superior parietal lobe, and increased FC with the ipsilateral cerebellum. Additionally, patients with MwoA demonstrated significantly decreased right SN-based FC with the right postcentral gyrus, left parietal lobule, and left superior frontal gyrus. Hypo-connectivity between the right SN and right postcentral gyrus was negatively correlated with disease duration (r = − 0.506, P = 0.004). Additionally, increased connectivity of the right RN to the ipsilateral cerebellar lobes was positively correlated with the Headache Impact Test-6 scores (r = 0.437, P = 0.016). Conclusions The present study suggested that patients with MwoA have disruption in their RN and SN resting-state networks, which are associated with specific clinical characteristics. The changes focus on the regions associated with cognitive evaluation, multisensory integration, and modulation of perception and pain, which may be associated with migraine production, feedback, and development. Taken together, these results may improve our understanding of the neuropathological mechanism of migraine.